Early Diagnosis: Ultra‐Early Diagnosis of Acute Myocardial Infarction in Rats Using Ultrasound Imaging of Hollow Double‐Layer Silica Nanospheres (Adv. Healthcare Mater. 3/2020). Issue 3 (5th February 2020) - Guo, Mengzhe; Du, Wencheng; Lyu, Nan; Chen, Xi; Du, Yan; Wang, Haibo; Yang, Dongzhi; Wu, Shihua; Liang, Jun; Pan, Yuanjiang; Tang, Daoquan
Abstract : Timely diagnosis of acute myocardial infarction (AMI) strongly impacts the survival rate of patients. In article number 1901155, Yuanjiang Pan, Daoquan Tang, and co‐workers report the development of a two‐shell hollow silica contrast agent useful for ultrasound (US) imaging, which is able to provide ultra‐early diagnosis of AMI.